Articulations of Womanism in Adichie's Purple Hibiscus and Emecheta's The Joys of Motherhood - Amartey, C. (University of Ghana, 2013)
Womanism as a variant of African feminism provides the platform for a holistic analysis of the works of African female writers. In this work, Ogunyemi’s womanist theory is read into the works of two Nigerian female writers, Chimamanda Adichie and Buchi Emecheta, authors of Purple Hibiscus and The Joys of Motherhood respectively. Undertaking a womanist reading of these two novels is aimed at ascertaining the different and similar ways these female novelists articulate womanist theory in the above mentioned novels through a comparative study. The work also aimed at finding out whether there is a continuity of womanist concerns between these two female novelists or otherwise. The conclusions drawn from this study are arrived at through a close reading of the two novels by looking at literary elements of characterization, narrative technique, tone, mood and setting. From the analysis of the two novels, it is clear that Adichie leans more towards challenging and usurping patriarchy while Emecheta valourizes traditional patriarchal society in her work. Adichie’s Purple Hibiscus also resounds with womanist hope as opposed to the tragic end that befalls Emecheta’s protagonist, Nnu Ego. However, both authors lean towards the ultimate womanist goal of unity and survival of males, females and children. The comparative analysis of the two novels only shows womanist continuity in of terms the two authors’ commitment to the ultimate goal of womanism. Apart from this, Adichie is more aggressive in questioning, criticizing and subverting patriarchal authority as compared to Emecheta.
Thesis (MPHIL) - University of Ghana, 2013